The Influence of Debt to Asset Ratio, Investment Opportunity Set, and Firm Size on Accounting Conservatism of PT. Jaya Real Property, Tbk 2016-2021 - Muhammad Heriansyah; Fazhar Sumantri; Robby Rabanni Rafsanjani; Rohim Setiawan; Alvandy Agung P.M (Institute of Computer Science (IOCS), 2022)
The objective of this research is to examine the analysis of factors have an impact on accounting conservatism in PT company. Jaya Real Property, Tbk period 2016-2021. Sampling is done by purposeful sampling method. Quarterly time series data for the period 2016-2021 is used as a sample. As a result, the total number of samples obtained is 24 samples. IBM SPSS Statistics 26 application was used to perform multiple regression analysis in this research. According to F test (simultaneously) results, the independent variables of debt-to-assets ratio, investment opportunity set and firm size all have an impact influence on accounting conservatism. Contingent the results of the partial t-test, perhaps inferred of debt-to-asset ratio and the set of investment opportunities have an impact on accounting conservatism, but firm size does not. significant movements. Out of results the experimental resolution also explain of the debt-to-asset ratio, the set of investment opportunities, and the capacity of the business have an important influence on the conservatism in quarterly accounting for the period 2016-2020.